2015
DOI: 10.1007/s00192-015-2837-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for persistent urodynamic stress incontinence following extensive pelvic reconstructive surgery with and without midurethral sling

Abstract: Overt USI with advanced POP together with low MUCP and FUL values have a higher risk of developing P-USI. Therefore, counseling these women is worthwhile while considering the type of mesh used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…It has been reported that patients of old age (>66 years), MUCP <60 mmH 2 O, and functional urethral length < 2 cm were at greater risk of developing de novo SUI after transvaginal pelvic reconstructive surgery. 8,13 Similarly, our study also showed that de novo SUI was more prevalent in elderly patients (≥70 years). Not only after transvaginal surgery but also after LSC, the prevalence of de novo SUI is significantly higher in patients with low MUCP (<40 cmH 2 O).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It has been reported that patients of old age (>66 years), MUCP <60 mmH 2 O, and functional urethral length < 2 cm were at greater risk of developing de novo SUI after transvaginal pelvic reconstructive surgery. 8,13 Similarly, our study also showed that de novo SUI was more prevalent in elderly patients (≥70 years). Not only after transvaginal surgery but also after LSC, the prevalence of de novo SUI is significantly higher in patients with low MUCP (<40 cmH 2 O).…”
Section: Resultssupporting
confidence: 78%
“…12 Some studies have examined preoperative bladder functions using urodynamic studies (UDS) as predictors of de novo SUI after POP surgery. 3,8,13,14 However, urodynamic parameters to predict risk of de novo SUI have been controversial. We have already reported the changes in UDS parameters before and after LSC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have highlighted the risk factors for mesh extrusion, including DM, hypertension, smoking, previous pelvic surgeries, concomitant hysterectomy, greater intraoperative blood loss, and surgery performed by a junior surgeon, with the protective factors being uterine preservation, with no mesh over the apex [16−19]. Although our concomitant hysterectomy rate was high at 63.9%, studies carried out by the same first author using various mesh kits with similarly high hysterectomy rates (67%−92%) have demonstrated that preoperative optimization of medical comorbidities, patient selection, reduction of mesh material, surgeon experience, and surgical technique-rather than concomitant hysterectomy-are the major factors for mesh exposure [16,20,21]. These measures, including tight requirements on preoperative glycated hemoglobin, exclusion of patients with previous radical pelvic surgeries, removal of the 2 middle arms with no mesh placed over the apex or posterior compartment, all surgeries performed by the same senior author (TSL) with a meticulous surgical technique, and minimizing intraoperative blood loss, were similarly employed in our current study.…”
Section: Discussionmentioning
confidence: 91%
“…Borstad's similarly show 27% of women cured of SUI after surgical repair of POP 32 . The persistence of SUI in 40% (27/68) of the patients without MUS is likely due to having MUCP < 60 cm H 2 O and FUL < 2 cm together with overt SUI and advanced POP 33 .…”
Section: Discussionmentioning
confidence: 99%